Hadith #4086 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Ali bin Mdrk al-Nkh'y علي بن مدرك النخعي; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Kharsha bin al-Hurr al-Fazari; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
A man was praying with his lower garment hanging down. The Messenger of Allah (ﷺ) said to him: Go and perform ablution. He then went and performed ablution. He then came and he said: Go and perform ablution. Then a man said to him: Messenger of Allah, what is the matter with you that you commanded him to perform ablution and then you kept silence ? He replied: He was praying while hanging down his lower garments, and Allah does not accept the prayer of a man who hangs down his lower garment.
Grade: Hasan

Hadith #4151 - Sunan Abi Dawud - Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Ali bin Mdrk al-Nkh'y علي بن مدرك النخعي; Ali ibn Abi Talib; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) never left in his house anything containing the figure of a cross without destroying it.
Grade: Sahih